The Supplementation Effect of Turmeric (Curcuma domestica Vahl.) and Brotowali (Tinosporacrispa L. Miers) Extract on Broiler Meat Quality - Rahadi, Syam; Indi, A.; Rahman, Rahman; Yadi, Y.; Kurniawan, W.; Mansur, Mansur (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The usage of natural feed additive be expected can increase meat quality and broilersperformance. This research was aimed to study interaction effect of turmeric and brotowali extractfeed supplementation on broiler meat quality.300 birds of Cobs broiler strain were used andseparated on 50 pens with 6 birds each pen and maintained until 42 days old. The research was usefactorial complete randomized design with first factor was turmeric extract levels (0; 0.2; 0.4; 0.6;and 0.8%), and the second factor was brotowali extract levels (0; 0.2; 0.4; 0.6; and 0.8%), so therewas 25 treatment combinations with two replications. The research parameters were meat pH,cooking loss (CS), dry matter (DM), and organic matter (OM). Result of research showed thatturmeric and brotowali extract supplementation have significant interaction effect on broiler meatDM content, but does not have effect on pH, CS, and OM content. Combination of 0.4% turmeric and0.2% brotowali extract supplementation was provide highest DM content, meanwhile on individualeffect, supplementation turmeric at 0.4% level has significant effect on SC parameter.Key Words: Turmeric, Brotowali, Broiler, Meat Quality